Early numeracy : assessment for teaching and intervention - Wright, Robert J. (Robert John), 1948-; Martland, Jim.; Stafford, Ann K. (London ; Thousand Oaks, Calif. : Paul Chapman, 2006)
This is a highly practical resource that will be appreciated by classroom and specialist teachers alike. It will provide teachers new to the Mathematics Recovery Programme with practical help and support to diagnose errors and misconceptions in early numeracy
1. Children, numeracy and mathematics recovery --
2. The learning framework in number --
3. The LFIN and the assessment interview schedule 1.1 --
4. The stages of early arithmetical learning (SEAL) --
5. Identifying the stages of early arithmetical learning --
6. Assessment interview schedule 1.2 --
7. Part C of the LFIN: assessment interview schedules 2.1 and 2.2 --
8. Assessment interview schedules 3.1 and 3.2 --
9. Recording, coding and analyzing the assessment interview schedules --
10. Linking the assessment to teaching --
Appendices --
Glossary.
Includes bibliographical references (p. [193]-196) and index.
BIED
Complimentary copy from BIED
Keywords: Numeracy -- Study and teaching (Elementary); Learning, Psychology of; Numeracy -- Study and teaching (Primary)